P10.07.B Differential YAP activity in human glioblastoma tumorspheres. (5th September 2022) - Kim, E; Oh, Y; Kang, S
Abstract: Background: Although glioblastoma (GBM) is the most common primary brain tumor, the best available treatment options are still associated with poor prognosis. Recently, the Hippo/YAP signaling pathway has been emerged as an important driver of GBM. Nevertheless, extensive studies have not yet been focused on the importance of phosphorylation event in regulating endogenous YAP activity in GBM. Here, we sought to elucidate that the modulation and stabilization of YAP/TAZ in Hippo pathway promotes GBM progression. Material and Methods: Expression patterns of YAP1, TAZ, CTGF, TEAD4 and LATS1 mRNA were confirmed in human normal and GBM tissue, and patient survival according to YAP1 expression was confirmed in TCGA and Severance cohort. The YAP1 expression patterns in several TSs were classified into SOH and AH according to transcriptome analysis and western blot. For each classified TSs, the characteristics of SOH and AH were comparatively analyzed through immunoprecipitation, nucleus fraction, TEAD4 luciferase assay, and confocal analysis. The effect of YAP1 knockdown/out and overexpression in SOH and AH TSs were measured by WST/ATP analysis, 3D invasion and neurosphere formation, and western blot. In addition, the drug reactivity of SOH and AH TSs was examined by treatment with the YAP1 inhibitors Peptide17 and verteporfin, and the effects of Peptide17, verteporfin and YAP1-shRNA were examined in in-vivo xenograft model. Results: YAP1 mRNA levels including TAZ, CTGF, TEAD4 and LATS1 were higher in GBM than in normal tissues. Through transcriptome analysis and western blot, TS can be divided into SOH and AH groups according to the expression level of CTGF, but not YAP1 level. In the case of SOH TS, the binding of TEAD4 was strong in immunoprecipitation, the ratio of YAP1 was higher in the nucleus in the nucleus fractionation and confocal analysis, and the luciferase activity of TEAD4 was high in the TEAD4 luciferase assay. On the other hand, in the case of TS of AH, the opposite trend was observed. When YAP1 was knocked down or out, the proliferation, invasion, and stemness of TS tended to be decrease more in SOH TS than in AH TS, and SOH TS showed more sensitive drug response even in Peptide17 and Verteporfin treatment. In the case of YAP1 overexpression, the opposite trend was observed in SOH TS. In the in-vivo xenograft model, injection of Peptide17, verteporfin, and YAP1-shRNA showed a tendency to increase the survival rate of mice. Conclusion: The association of YAP has been described in several cancers, but there has been no study comparing GBM TS by YAP expression and classifying it at the functional level. Now, for the first time, we show that the characteristics of GBM TS can be predicted according to the expression value of YAP, respectively, and YAP is expected to be applied as an important prognostic factor for GBM treatment in the future.